Data on minerals and crystallinity index of quartz in rock samples collected from Paleolithic archaeological site of Attirampakkam, Tamil Nadu - A. Tamilarasi (Elsevier, 2021)
In the present work, rock samples were collected from Paleolithic archaeological site of Attirampakkam, Tamil Nadu, India to assess the mineralogical composition using Fourier transform infrared-spectroscopic (FT-IR) technique and X-Ray Diffraction Spectrometry (XRD). The quartz, kaolinite, montmorillonite, calcite, orthoclase, microcline and illite minerals are identified in rock samples and crystallinity index of quartz (SiO2) is estimated for all the samples by comparing the ratio of intensity of the characteristic peak at 778 and 695 cm–1 using FT-IR spectrum. In rock samples, calculated crystallinity index of quartz is greater than the 1 from FT-IR spectrum and it shows that the distribution is disordered in nature. Additionally, some more minerals such as hematite and rutile are identified in rock samples by X-ray diffraction technique. This extensive study shows that archeological rock samples are wide variation in mineral composition.